2020
DOI: 10.24875/acme.m19000059
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac sympathetic denervation for conventional treatment refractory arrhythmias

Abstract: Objective: Cardiac sympathetic denervation (CSD) using video-assisted thoracoscopy is a therapeutic alternative for cardiac arrhythmias refractory to conventional treatment in patients with ventricular structural heart disease, mainly due to ischemia, and in patients with hereditary conditions associated with sudden death such as long QT syndrome. In general, it is performed in cases with recurrent episodes of ventricular tachycardia or electrical storm, in spite of conventional treatment. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…16 The other, a case series of six patients in the city of Cali, reported a decrease of symptoms in four patients. 17 Other studies have reported effectiveness ranging from 70% to 80% within the first month to the first year after VAT-CSD. [18][19][20][21][22] This study evaluated symptom control by measuring the mean number of ICD shocks in the month before and after surgery, as well as ED visits related to arrhythmia before and after VAT-CSD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…16 The other, a case series of six patients in the city of Cali, reported a decrease of symptoms in four patients. 17 Other studies have reported effectiveness ranging from 70% to 80% within the first month to the first year after VAT-CSD. [18][19][20][21][22] This study evaluated symptom control by measuring the mean number of ICD shocks in the month before and after surgery, as well as ED visits related to arrhythmia before and after VAT-CSD.…”
Section: Discussionmentioning
confidence: 95%
“…[ 16 ] The other, a case series of six patients in the city of Cali, reported a decrease of symptoms in four patients. [ 17 ] Other studies have reported effectiveness ranging from 70% to 80% within the first month to the first year after VAT-CSD. [ 18 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…These patients, exhibiting a higher risk for SCD due to arrhythmias such as atrioventricular block and sinus arrest, frequently benefit from ICDs as primary treatment, especially when β-blockers fail to prevent syncope or ventricular tachycardia. Guidelines suggest ICD placement as a class II indication for LQTS patients experiencing life-threatening arrhythmias despite β-blocker therapy, highlighting its importance in preventing sudden death among high-risk groups [ 24 ].…”
Section: Reviewmentioning
confidence: 99%